2017
DOI: 10.1103/physrevb.95.174509
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium properties of superconducting niobium at high magnetic fields: A possible existence of a filamentary state in type-II superconductors

Abstract: The standard interpretation of the phase diagram of type-II superconductors was developed in 1960s and has since been considered a well-established part of classical superconductivity. However, upon closer examination a number of fundamental issues arise that leads one to question this standard picture. To address these issues we studied equilibrium properties of niobium samples near and above the upper critical field Hc2 in parallel and perpendicular magnetic fields. The samples investigated were very high qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…In particular, the coherence length calculated from measured D using Eq. (16) agrees well with that obtained from the magnetic field profile measured in [36]. Here we confine our discussion by limiting cases.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…In particular, the coherence length calculated from measured D using Eq. (16) agrees well with that obtained from the magnetic field profile measured in [36]. Here we confine our discussion by limiting cases.…”
supporting
confidence: 77%
“…H t in this graph corresponds to H cr in our notations. The tubular phase mentioned in the caption most probably corresponds to the filament state discussed in [36].…”
Section: Superfluids and Superconductors 100mentioning
confidence: 99%
“…(21) and trial wave function of the form Eq. (20). After multiplication by ∆(x) the integral on the left-hand-side of Eq.…”
Section: Appendix A: Integralsmentioning
confidence: 99%
“…It was revealed that the H c3 /H c2 ratio is not a universal number but rather a complicated function that exhibits pronounced dependence on both T and the mean-free time τ mediated by disorder scattering. Niobium became essentially a paradigmatic material to study various phenomena associated with surface superconductivity and multiple experiments continue to follow [14][15][16][17][18][19][20]. Naturally over time experimental efforts on surface superconductivity branched into different directions.…”
Section: Introductionmentioning
confidence: 99%
“…(54) is derived assuming that superconductivity vanishes completely at H c2 , i.e. neglecting the filamentary state occurring at H c2 < H 0 < H c3[8,75] 55. In this work the type-II superconductivity was solidly established for the first time.…”
mentioning
confidence: 99%